2007
DOI: 10.1108/14691930710742835
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital performance of quoted banks on the Istanbul stock exchange market

Abstract: PurposeThe purpose of the paper is to obtain measure of the intellectual capital (IC) performance of quoted banks on the Istanbul Stock Exchange Market (ISE) in Turkey for the period 1995‐2004 and test the effect of the intellectual capital performance on profitability.Design/methodology/approachData required for calculating intellectual capital efficiencies were obtained from the ISE for the period 1995‐2004. The authors measured the intellectual capital performance of quoted banks in ISE using the efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 20 publications
12
110
1
3
Order By: Relevance
“…The study has also provided confirmatory evidence of the dominance of human capital efficiency to the value of VAIC TM consistent with other prior studies (Mohiuddin et al, 2006;Mavridis, 2005;Goh, 2005;Kamath, 2007;Muhammad & Ismail, 2009;Joshi et al, 2010). The study has indicated that human capital efficiency scores over the study period contributed about two thirds to the value of VAIC TM , thus suggesting that human capital is very important factor than physical capital for banks (Yalama and Coskun, 2007). The results assent to the fact that although physical capital is essential for banks to operate, it is the intellectual capital that determines the quality of services provided to customers (Goh, 2005).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The study has also provided confirmatory evidence of the dominance of human capital efficiency to the value of VAIC TM consistent with other prior studies (Mohiuddin et al, 2006;Mavridis, 2005;Goh, 2005;Kamath, 2007;Muhammad & Ismail, 2009;Joshi et al, 2010). The study has indicated that human capital efficiency scores over the study period contributed about two thirds to the value of VAIC TM , thus suggesting that human capital is very important factor than physical capital for banks (Yalama and Coskun, 2007). The results assent to the fact that although physical capital is essential for banks to operate, it is the intellectual capital that determines the quality of services provided to customers (Goh, 2005).…”
Section: Resultssupporting
confidence: 79%
“…Mondal and Ghosh (2012) described intellectual capital as "intangible assets or intangible business factors of the company, which have a significant impact on its performance and overall business success, although they are not explicitly listed in the balance sheet (if so, then under the term goodwill)." According to Yalama and Coskun (2007) intellectual capital is "something which already exists in a firm but cannot be seen on its balance sheet exactly, a competitive advantage over the firm's competitors, future values and includes all its intangible assets, the value of knowledge, information, intellectual property and experience, a key factor influencing the future value of the firm." Cabrita and Vaz (2005) simply stated that intellectual capital is a matter of creating and supporting connectivity between all sets of expertise, experience and competences inside and outside the organization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although some researchers [23,8,25] emphasized the role of intellectual capital in explaining the difference between book and market values of companies, the current study, like some similar studies [15,14,10], has not find any signs regarding the relationship between intellectual capital and market value of companies. On the other hand, as some researchers [34,30,26,17,12,10] confirm the role of intellectual capital in explaining the profitability, the current study also showed the mentioned relationship. This study includes significant themes for practitioners and managers of pharmaceutical companies and researchers who are interested in the topic of intellectual capital.…”
Section: Conclusion and Recommendationsmentioning
confidence: 57%
“…Al-Matari, et al, 2014,Byrd & Hickman, 1992Chen et al, 2005;Drobetz et al, 2003;Gazor et al, 2013;Hossain et al, 2000;Ku Ismail & Abdul Karem, 2011;Jafari, 2013;Ping et al, 2006;Kujansivu & Lonnqvist, 2007;Mahoney & Roberts, 2002;Nazari & Herremans, 2007;Oliver & Porta, 2006;Rosenstein & Wyatt, 1990;Waddock & Graves, 1997;Yalama & Coskun, 2007) have used return on asset (ROA) and return on equity (ROE) as a measure of financial performance either alone or in addition to other measures in their studies of the influence of intellectual capital and corporate governance of firms Return on asset (ROA) is calculated by dividing net income by total assets whereas return on equity (ROE) is calculated by dividing net income by total equity.…”
Section: Research Methods and The Study Modelsmentioning
confidence: 99%